An Ancient Mega-Project in North Jordan: The Fortress of Tell Ushayer - Bonatz, Dominik (Palestine exploration quarterly, 2026)
An archaeological site in northern Jordan, close to Irbid, with massive stones from a fortification wall protruding from its surface, is judged to be fairly recent by visitors; the inhabitants of the nearby village are convinced it is modern. Yet the investigations carried out by the Freie Universität Berlin at Tell Ushayer, which began in 2018, tell a different story. What seemed at first sight to be a defensive wall surrounding the top of the mound has turned out to be part of a complex, monumental fortification system. The circular wall alternates with massive buttresses, and a gate opens to the east shielded by an outer bastion that also limits the course of the ramp, which in turn is further protected by a second wall and watch towers. The excavated remains point to continuous use and modification of the fortification system during the Iron Age, yet the foundation date of this impressive structure so far remains elusive. This paper presents recent results from the ongoing project at the site and insights into the occupation sequence.